Synergistic effect of supported ZnO/Bi2O3 heterojunctions for photocatalysis under visible light. (June 2018) - Medina, J.C.; Portillo-Vélez, N.S.; Bizarro, M.; Hernández-Gordillo, A.; Rodil, S.E.
Abstract: In this article we report a novel and affordable approach to fabricate supported ZnO/Bi2 O3 heterostructures for the visible-light photocatalytic degradation of organic compounds. This 2D-heterojunction was produced by depositing Bi2 O3 dots by sputtering onto a ZnO thin film deposited on glass substrates by spray pyrolysis. The structural, morphological, electronic and optical properties were studied and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), electrochemical impedance and UV–vis spectroscopy, respectively. Chemical composition spectra and images of the interface were obtained by X-ray photoelectron spectroscopy (XPS). Photocatalytic experiments were performed for the degradation of indigo carmine (IC) under UV and visible light irradiation, whilst the percentage of mineralization was measured by total organic content determination. It was found that the ZnO/Bi2 O3 bi-layers with heterojunction showed enhanced photodiscoloration and mineralization under visible light compared to the ZnO and Bi2 O3 films separately. This is due to a synergistic effect in which Bi2 O3 extends the absorption range of the film to the visible region and the proper alignment of the electronic band edges induces charge separation with the subsequent reduction in the recombination rate. Moreover, through a careful analysis of the absorbance spectra of the IC dye solutions and the energetics for the different photocatalytic reactions, the mechanisms for the degradation routes followed under each irradiation source and material is proposed. Graphical abstract: Highlights: ZnO/Bi2 O3 heterojunction was produced by spray pyrolysis and sputtering techniques. Dots of δ-Bi2 O3 on ZnO film extend the light absorption into the visible range. High photocatalytic response of ZnO/Bi2 O3 was achieved by the synergistic effect. The OH radical produced by ZnO/Bi2 O3 are responsible of 43% of mineralization.